1977
DOI: 10.1139/b77-190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of habitat and substrate quality on Douglas fir litter decomposition in western Oregon

Abstract: Linear regression models were developed for Douglas fir needle, female cone, branch, and bark decomposition in seven stands representing four mature vegetation types in western Oregon. Rate constants (k) for annual weight loss of needles ranged from 0.22 to 0.31 year−1, from 0.047 to 0.083 year−1 for cones, from 0.059 to 0.089 year−1 for branches, and from 0.005 to 0.040 year−1 for bark. The decomposition constant (k) of needles had a negative linear correlation (P < 0.01) with maximum plant moisture stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
152
5

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(167 citation statements)
references
References 15 publications
10
152
5
Order By: Relevance
“…Swift et al (1979), Melillo et al (1982), Berg and Lundmark (1987), and Wang et al (2008) have commented on the effects of lignin and nitrogen content on litter decomposition; our results showed that lignin was more critical for litter decomposition than N content. This result agrees with Bollen (1953) and Fogel and Cromack (1977), who suggested that lignin is more important than N in the relationship between chemical constituents and the decomposition rate. The lignin content seems to be a limiting factor for litter decomposition at a later stage, after rates.…”
Section: Discussionsupporting
confidence: 92%
“…Swift et al (1979), Melillo et al (1982), Berg and Lundmark (1987), and Wang et al (2008) have commented on the effects of lignin and nitrogen content on litter decomposition; our results showed that lignin was more critical for litter decomposition than N content. This result agrees with Bollen (1953) and Fogel and Cromack (1977), who suggested that lignin is more important than N in the relationship between chemical constituents and the decomposition rate. The lignin content seems to be a limiting factor for litter decomposition at a later stage, after rates.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrogen content of plant material is important in controlling rate of decomposition according to some studies (Findlay 1934, Millar et al 1936, Merrill and Cowling 1966. Other studies indicate that lignin content of the litter exerts more control over the rate of decomposition than does nitrogen (Bollen 1953, Fogel andCromack 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors control leaf litter decomposition, including climate [2], topography [3,4], chemical characteristics of leaf litter [5,6], and terrestrial microbiota [7]. Among those factors, climate, especially temperature and precipitation, is a dominant factor determining leaf litter decomposition patterns in regions experiencing distinct seasonal climate change [8].…”
Section: Introductionmentioning
confidence: 99%